Genomic epidemiology of nosocomial carbapenemase-producing Citrobacter freundii in sewerage systems in the Helsinki metropolitan area, Finland - Heljanko, Viivi; Johansson, Venla; Räisänen, Kati; Anttila, Veli-Jukka; Lyytikäinen, Outi; Jalava, Jari; Weijo, Irma; Lehtinen, Jaana-Marija; Lehto, Kirsi-Maarit; Lipponen, Anssi; Oikarinen, Sami; Pitkänen, Tarja; et al. (Frontiers in Microbiology, 2023)
Multi-drug resistance is emerging in Citrobacter freundii, which is – because of the recent outbreaks – the third most common carbapenemase-producing (CP) Enterobacteriaceae in humans in Finland. We studied whether wastewater surveillance (WWS) can detect CP C. freundii strains causing infections by conducting a genomic comparison of isolates from the human specimen, hospital environment, and untreated municipal wastewater. We also examined the persistence of CP C. freundii in the hospital environment and the effects of its eradication attempts. CP C. freundii was isolated with selective culturing from the hospital environment, hospital wastewater, and untreated municipal wastewater in Helsinki, Finland, during 2019¬–2022. Species were identified with MALDI-TOF, and presumptive CP C. freundii isolates were subjected to antimicrobial susceptibility testing and further characterized by whole genome sequencing. Altogether 27 blaKPC-2-carrying C. freundii were detected from the hospital environment (ST18; n=23 and ST8; n=4). From the untreated municipal wastewater, 13 blaKPC-2-carrying (ST8) and five blaVIM-1-carrying (ST421) C. freundii were identified. CP C. freundii was not identified in hospital wastewater. A genomic comparison between the recovered isolates and a selection of isolates from human specimens from two hospitals located in the same city revealed three clusters (cluster distance threshold ≤10 allelic difference). The first cluster consisted of ST18 isolates from the hospital environment (n=23) and human specimens (n=4), the second consisted of ST8 isolates from the hospital environment (n=4), untreated municipal wastewater (n=6), and human specimens (n=2), and the third with ST421 isolates from the untreated municipal wastewater (n=5). Our results support previous studies that suggest that the hospital environment may act as a source of transmission of CP C. freundii in clinical settings and that eradication of CP Enterobacteriaceae from the hospital environment is challenging. Our findings also show that CP C. freundii is persistent throughout the sewerage system and demonstrate the potential of WWS for CP C. freundii.